Comparative Analysis of Al-Miftah and Al-Jurumiyah Methods in Accelerating Arabic Literacy Acquisition: A Study on Turath Reading Skills - Zulfan Syahansyah; Abdurrahman; Naser Ali Abdulghani (CV. Creative Tugu Pena, 2025)
The low level of Turath literacy caused by the complexity of classical grammar necessitates effective methodological innovations for novice learners. This study aims to compare the effectiveness of the Al-Miftah method and the Nahwu Putih Al-Jurumiyah scheme in enhancing the ability to read kitab kuning (classical Islamic texts). Utilizing a quasi-experimental non-equivalent control group design, the research was conducted at Pondok Pesantren Raudlatul Ulum 1 through purposive sampling. Data analysis using the Independent Sample T-Test and Repeated Measures ANOVA revealed that Al-Miftah is significantly superior in terms of comprehension speed and functional reading fluency. Conversely, the Nahwu Putih Al-Jurumiyah method contributes more significantly to the accuracy of I’rab (grammatical parsing) and demonstrates more stable long-term memory retention consistency (with a decline of only 5.0% compared to 12.0% for Al-Miftah). These findings substantiate a trade-off between cognitive speed and analytical depth. The impact of this research provides a new framework for Islamic educational institutions to integrate both methods, creating an accelerated Arabic literacy system that is both agile and precise for contemporary learners.